Eco-friendly alumina suspensions for tape-casting process. Issue 16 (December 2017) - Marie, Jérémy; Bourret, Julie; Geffroy, Pierre-Marie; Smith, Agnès; Chaleix, Vincent; Chartier, Thierry
Abstract: The aim of this study is focused on the elaboration of new bio-based alumina concentrated suspensions with rheological properties adapted to the tape casting process and with low environmental impact. Natural polymers extracted from plants were identified as promising candidates in order to substitute the classical organic additives. The aqueous suspensions were prepared from bio-polymer additives. The interactions between different organic additives with alumina were characterized by zeta-potential and quartz crystal microbalance measurements. The influence of the incorporation order of the different organic additives on the viscosity of the suspension was evaluated. Then, mechanical properties of the green and sintered tapes were determined in relation with the nature of bio-polymer additives.